Indolent T-Cell Lymphoproliferative Disease of the GI Tract: Insights for Better Diagnosis, Prognosis, and Appropriate Therapy - Küçük, Can; Wei, Li; You, Hua (Frontiers in Oncology, 2020)
Indolent T-cell lymphoproliferative disease of the gastrointestinal tract (indolent GI T-LPD) is a benign neoplasm of CD4+ or CD8+ T cells that form primary tumors in the GI tract. Indolent GI T-LPD has recently been provisionally recognized as a distinct entity by the 2016 revision of the WHO classification of lymphoid neoplasms. Appropriate diagnosis of these cases is challenging as they may be misdiagnosed as T cell lymphoma that has an aggressive clinical course. Consequently, aggressive therapeutic approaches were usually chosen to treat these cases with no obvious benefit for most of the patients and potential side effects. Moreover, inflammatory diseases of the GI tract with similar symptoms may lead to misdiagnosis that leads to delays in administration of proper therapeutics against these cases. Therefore, it is of utmost importance to identify prognostic genetic biomarkers at the time of diagnosis for optimal medical care of these patients. TCR clonality analyses may not be useful for distinguishing these benign neoplasms from aggressive gastrointestinal T cell lymphomas; however, genetic tests may prove useful as recurrent STAT3-JAK2 fusions, which may have diagnostic, prognostic or therapeutic value, have recently been identified. However, there is still lack of comprehensive information on the genetic and epigenetic factors associated with pathogenesis of indolent GI T-LPD. In this mini-review, we focus on the so far reported literature on indolent GI T-LPD cases, and discuss future directions for better differential diagnosis, risk stratification, and therapeutic target discovery with a special focus on the genetic and epigenetic alterations.